Basic Botany - Avery, David F.; Smith, Dwight G. (Simon and Schuster Custom Publishing, 1994)
Keywords: Botany; dept.egm; faculty_collection

Zoology Laboratory Guide - Avery, David F.; Nelson, Vernon A.; Pellegrino, Peter Edward; Smith, Dwight G.; Turko, Alexander A.; Burian, Steven K.; Green, Laura A.; Duman, Mathew (Southern Connecticut State University, 1994)
Keywords: Laboratory manuals; Zoology; dept.egm; faculty_collection

Hartshorne,richard, 1899-1992 - in-memoriam - Martin, GJ (Annals of the Association of American Geographers, 1994)
8 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1994PH93800007
Keywords: dept.egm

Geography and the human spirit - buttimer,a - Martin, GJ (Professional Geographer, 1994)
tex.unique-id: ISI:A1994NQ42000015
Keywords: dept.egm; ⛔ No DOI found

Pioneers of modern geography - translations pertaining to german geographers of the late 19th and early 20th centuries - west,rc - Martin, GJ (Professional Geographer, 1994)
tex.unique-id: ISI:A1994MW89600038
Keywords: dept.egm; ⛔ No DOI found

Tagging and migration of the American lobster Homarus americanus - Haakonsen, H. O.; Anoruo, A. O. (Reviews in Fisheries Science, 1994)
Three types of tags, external, internal, and sonic, have been used to study migration of the American lobster Homarus americanus. Tag loss and interpretation of returned tag data are serious problems associated with internal and external tags. Lobster tracking using sonic tags is still in the pilot stage. Lobster migration is redefined to include horizontal and vertical displacements. Depth of displacement is a more reasonable measurement of lobster migration than horizontal distance traveled. Two distinct lobster populations are discernable based on their ecological habitation and migratory behavior. Evidence in this review suggests that the deep-sea lobster migrates, whereas the coastal lobster may move within a limited range. © 1994, Taylor & Francis Group, LLC. All rights reserved.
20 citations (Crossref) [2023-10-31] Citation Key Alias: pop00045 tex.type: [object Object]
Keywords: Homarus americanus; coastal lobster; deep-sea lobster; dept.egm; migration

Recent contributions of the United Nations to political geography - Glassner, Martin Ira (Political Geography, 1994)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-931-043-628-079 tex.type: [object Object]
Keywords: dept.egm

The tide flows on - Glassner, Martin Ira (Ocean Yearbook Online, 1994)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/045-497-077-820-496
Keywords: dept.egm